Effect of epigallocatechin-3-gallate on acrylamide-induced oxidative stress and apoptosis in PC12 cells. (October 2017) - He, Y; Tan, D; Mi, Y; Bai, B; Jiang, D; Zhou, X; Ji, S
Acrylamide (ACR) is a chemical intermediate utilized in industry. ACR is also formed during heating of foods containing carbohydrates and amino acids. Therefore, humans are widely exposed to ACR, and ACR neurotoxicity in humans is a significant public health issue attracting wide attention. In this study, we investigated the potential neuroprotective effects of epigallocatechin-3-gallate (EGCG), the most abundant polyphenolic compound in green tea, in PC12 cells treated with ACR. ACR-treated PC12 cells pretreated with various concentrations of EGCG (2.5, 5 and 10 μM) for 24 h had increased viability and acetylcholinesterase activity and reduced apoptosis and necrosis compared to cells exposed to ACR alone. EGCG reduced the expression of bax mRNA, decreased cytochrome c release, reduced intracellular calcium levels, inactivated caspase 3 and increased mitochondrial membrane potential, suggesting that EGCG prevents ACR-induced apoptosis through a mitochondrial-mediated pathway. In addition, EGCG inhibited the formation of reactive oxygen species and lipid peroxidation while enhancing superoxide dismutase activity and glutathione levels, thereby reducing oxidative stress. Our results indicate that pretreatment of PC12 cells with EGCG attenuates ACR-induced apoptosis by reducing oxidative stress. Therefore, drinking green tea may reduce nerve injury induced by ACR.